Influence of parental income and gender on parental involvement in the education of secondary school children in Sri Lanka: a comprehensive investigation - Careemdeen, Jalal Deen (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research explores the intricate interplay of parental involvement in the education of secondary school children in Sri Lanka, with a particular focus on the intertwined influence of parental income and Gender. The study aims to unravel the complex relationships between parental income, Gender, and parental involvement and how these factors intersect within the educational context. The research is grounded in the backdrop of socioeconomic challenges and gender disparities in Sri Lanka's secondary education system, emphasising the importance of parental engagement in addressing these issues. The study's methodology involved a survey-based quantitative research design, and data analysis included descriptive and inferential statistics. The findings reveal that while parental income may not significantly impact overall involvement, it does influence various dimensions of parental participation. Gender-related variations in involvement are also evident, highlighting the importance of addressing disparities in educational support. These insights call for tailored strategies and policies to foster equitable involvement in education. The study offers valuable implications for educational policies and interventions, emphasising the need for comprehensive assessments of parental involvement, contextual analysis, and a focus on promoting equity and inclusivity in education. Ultimately, this research contributes to a deeper understanding of parental involvement in the complex educational landscape of Sri Lanka, with the goal of ensuring equal opportunities and success for all secondary school children, irrespective of their gender or socioeconomic background.